INOVASI MODEL PEMBELAJARAN PAI INTEGRATIF ANTARA KELAS DAN LINGKUNGAN ALAM DI SDIT ALAM NURUL ISLAM 2 NGAWI - Budi Sunariyanto; Kuni Fatonah; Muh. Zakki Amrulloh; Alan Lutfi Gesang Saputra; Jefri Mardiansyah A (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to describe Islamic Religious Education (IRE) learning conditions, analyze the use of the natural environment as a learning resource, and design and test an integrative IRE learning model at SDIT Alam Nurul Islam 2 Ngawi. The study employed mixed methods within a modified Borg and Gall Research and Development design. Data were collected through observation, in-depth interviews, documentation, and questionnaires, then analyzed qualitatively and quantitatively. The findings show that initial learning was dominated by lectures and memorization and had not optimized the natural environment. The INSPIRASI model comprises three phases: classroom concept exploration, nature-based exploration and spiritual reflection, and action with value internalization. Its application increased cognitive scores from 65.2 to 82.7, religious attitude scores from 70.1 to 85.4, and character behavior scores from 68.8 to 83.9. A paired-sample t-test for the cognitive domain yielded t = 8.45 and p < .001. The model effectively strengthened students' understanding, religious attitudes, environmental awareness, and Islamic character.